2021
DOI: 10.1007/s00795-021-00298-2
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of 16S rRNA for identification of invasive bacterial pathogens in a formalin-fixed paraffin-embedded placental specimen: a case report of perinatal fulminant Streptococcus pyogenes infection

Abstract: Intrauterine infection is one of the most important causes of maternal death. In perinatal emergency, we often miss an opportunity to obtain culture specimens. In this study, we tried to examine whether we investigated whether bacteria causing infection can be detected from a formalin-fixed paraffin-embedded (FFPE) placental specimen. We examined the placenta from a maternal invasive infection that resulted in infectious abortion at 18 weeks of gestation. The case was diagnosed by acute fever and abdominal pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Regarding the design of the studies, in three, an initial prospective design was proposed for the inclusion of the patients and the collection of the sample which were all from the pediatric population ( 33 35 ); however, in all the studies, the mNGS analysis of the collected samples was conducted retrospectively on the samples which were stored and frozen. Two studies were case reports which were from the neonate population ( 36 , 37 ). The characteristics of the admitted studies are shown in Tables 1 , 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the design of the studies, in three, an initial prospective design was proposed for the inclusion of the patients and the collection of the sample which were all from the pediatric population ( 33 35 ); however, in all the studies, the mNGS analysis of the collected samples was conducted retrospectively on the samples which were stored and frozen. Two studies were case reports which were from the neonate population ( 36 , 37 ). The characteristics of the admitted studies are shown in Tables 1 , 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies include a small number of patients, except for the study by Anh et al (34), which analyses samples from 388 children. On the other hand, the analysed samples in the studies were blood (33)(34)(35)(36)(37) and cerebrospinal fluid (34,36). The Anh study had the particularity of analysing, in addition to the blood samples and CFS, samples of the pharyngeal swab, tracheal aspirate and Stool (34).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Operational taxonomic units (OTUs) were constructed after quality filtering of the paired‐end reads. The OTUs were assigned to taxa using the database reported in a previous study 11 . Bacteria that were frequently observed in the negative control were grouped as background bacterial contamination (Supplemental Data 1), and after screening of the samples, the background‐contaminated bacteria were excluded from the microbiome profile.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from the endometrial and vaginal secretions of pregnant and nonpregnant patients using a previously reported protocol (Kyono et al, 2018b;Mariya et al, 2021). UltraPure™ DNase/RNase-Free Distilled Water (Thermo Fisher Scientific Inc., Waltham, MA, USA) was used as a negative control.…”
Section: Dna Extraction Sequencing and Analysismentioning
confidence: 99%